GAMBARAN SINDROMA PRAHAID PADA REMAJA - Bungasari, Septa Ayu; Tendean, Hermie M. M.; Suparman, Eddy (e-CliniC, 2015)
Abstract: Menstruation issue is a common gynecological issue experienced by adolescents. One of disorders linked with menstruation is premenstrual syndrome. According to ICD-10 issued by WHO, premenstrual syndrome included to gynecology disorder associated with female genital organs and menstrual cycle. Premenstrual syndrome can interfere with daily activities, interpersonal relationship, occupational achievement and educational performance due to impaired attention in class and absence from school. The study used survey descriptive method with questionnaire tool carried out among 54 female students of the first semester in Faculty of Medicine, University of Sam Ratulangi, within academic year of 2014-2015. The results showed that of the 54 female students, most of them were 18 years old (48.1%), predominant types of symptom was psychology symptom in 54 samples (100%), predominant psychology symptom was mood swing in 52 samples (96.3%), predominant physical symptom was acne problem in 45 samples (83.3%) and predominant behavioral symptom was argumentative in 17 samples (31.5%). Keywords: premenstrual, syndrome, adolescent, teenage Abstrak: Masalah yang timbul pada haid merupakan masalah ginekologi yang sering dikeluhkan remaja. Salah satu gangguan yang berhubungan dengan haid adalah sindroma prahaid. Menurut ICD ke-10 yang dikeluarkan WHO, sindroma prahaid tercantum sebagai kelainan ginekologi yang terkait dengan organ kelamin wanita dan siklus haid.Kumpulan gejala yang dirasakan menjelang haid mengganggu aktivitas sehari-hari, hubungan interpersonal, hasil kerja dan prestasi akademik karena kurang perhatian dalam kelas dan sering tidak hadir. Penelitian ini menggunakan metode survei deskriptif dengan alat kuesioner yang dilakukan pada 54 mahasiswi semester 1 Fakultas Kedokteran Unsrat tahun ajaran 2014-2015. Berdasarkan penelitian pada 54 mahasiswi, didapatkan distribusi umur responden terbanyak ialah 18 tahun (48,1%); jenis gejala yang paling dominan muncul ialah gejala psikologis sebanyak 54 orang (100%); gejala psikologis terbanyak ialah perubahan mood sebanyak 52 orang (96.3%); gejala fisik terbanyak ialah timbul jerawat sebanyak 45 orang (83,3%); dan gejala perilaku terbanyak ialah suka menentang sebanyak 17 orang (31,5%). Kata kunci: prahaid, sindroma, remaja